What do nursing students expect from ICT in their learning and practice? - Sá, C.; Nabais, A.; Oliveira, A. (11th annual International Conference of Education, Research and Innovation, ICERI 2018, 2018)
The development of science due to the progressive scientific and technological discoveries led to significant changes in the people health care, requiring a more complex and demanding nursing care. Nowadays, in the upbringing of a nurses, they may use several equipment and educational technologies that benefit from information and communication technologies (ICT), whose goal is to facilitate the learning process. Most of the emerging tools provide high-quality learning experiences effectively and economically. The use of ICT supplements traditional instructional methods. The role of nursing education is to prepare the future nurses to work in several environments. So, nursing schools need to prepare nurses to work with different technologies and applications (apps), in a digital world. In this paper, our main goal is understand the importance attributed to ICT in the learning process among nursing students. According to the methodology adopted we performed individual interviews with nursing students. Data were treated through context analyses, after being transcribed and analyzed, using a typical statistical software. Findings revealed that students emphasize the importance of ICT in the academical process the advantages it brings to them as future health professionals. Nursing students most usually use the computer and cell phone with the goal of doing research, gather information and interact with peers, allowing communication but an autonomous study. ICT is understood as means for a quick and easy access to information, facilitating the learning process and contributing to take decisions in the nursing care based upon scientific evidences. It is also central in the communication between nurse and patient, and between health professionals, promoting the continuity of care and support people with chronic diseases. In sum, nursing students consider ICT essential as a facilitator in the research and communication, not only in an academic context (in theoretical and practical classes) but also in health units context.